KEHIDUPAN EKONOMI PETANI SAYUR DI DAERAH LIPOSOS II KOTA JAMBI 1996-2007 - Mery Ardiyanti, Ujang Hariyadi (Istoria: Jurnal Ilmiah Pendidikan Sejarah Universitas Batanghari, 2018)
Abstract The purpose of the research to describe how the economic activities of vegetable farmers in Liposos II and the extent to which the influence of vegetable plantations on the economic life of vegetables in Liposos 1996-2007. The method used is historical research methods include heuristic stages, criticism, interpretation and historiography. Historical sources used of local archives and interviews and written literature. Local archives include Liposos II archives. Interviews were conducted with the parties who have a relationship with this research that is the vegetable farmers who are in Liposos II, ranging from government, farmers as well as owners of vegetable land.The approach used is the economic approach, among others, to determine the income and profits of farmers. In addition there is also a sociological approach to see the relationship between vegetable farmers with other vegetable farmers also see the relationship between farmers. The results showed that vegetable planting in Liposos II is still traditional and small scale but this activity still gives a positive influence for the life of the population, especially for those who are directly involved. These influences include improving the welfare of farmers as well as owners of vegetables that create jobs and reduce unemployment. Keywords: Economic Life of Vegetable Farmer, In Liposos